Efeitos da regulação no custo de aquisição de energia elétrica no Brasil - Schutze, Amanda Motta (2010)
Over the past twenty years, the Brazilian Electric Sector (SEB) went through profound changes including two structural changes. The first, in 1995, made the transition from a centralized model with state-owned companies operating under a monopoly model to a free market model emphasizing the privatization of the sector. The second, in 2004, recovers the state's role in planning the sector expansion, establishes the coexistence of state and private companies and seeks to promote affordable tariffs. The main reason for the changes is the need for investment to expand the electric power supply. This paper aims to present these structural changes, to display the current operation of the electric power sector and to consider the issue of the end of the generation concessions from 2015 on. The federal government vagueness between bidding or extending these concessions creates uncertainties thus postponing the investments and causing losses to the country.